2021
DOI: 10.1177/1559827620984995
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sports-Related Concussion: An Approach to Care

Abstract: Sports-related concussion (SRC) is a common sports injury in children and adolescents. With the vast amount of youth sports participation, an increase in awareness of concussion and evidence that the injury can lead to consequences for school, sports and overall quality of life, it has become increasingly important to properly diagnose and manage concussion. SRC in the student athlete is a unique and complex injury, and it is important to highlight the differences in the management of child and adolescent conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 185 publications
(333 reference statements)
0
7
0
Order By: Relevance
“…When presented with a patient experiencing academic decline, referral to neuropsychology should be considered for a comprehensive assessment of executive function. Pediatric neuropsychologists are trained in assessing, diagnosing, supporting, and rehabilitating children with cognitive, learning, neurological, or psychiatric disorders 45 . While the availability of neuropsychology is often limited, neuropsychologic testing can be helpful in identifying any underlying or exacerbation of a neurocognitive disorder requiring further therapeutic support (i.e., medication or speech or cognitive therapy).…”
Section: Rehabilitation and Long-term Managementmentioning
confidence: 99%
“…When presented with a patient experiencing academic decline, referral to neuropsychology should be considered for a comprehensive assessment of executive function. Pediatric neuropsychologists are trained in assessing, diagnosing, supporting, and rehabilitating children with cognitive, learning, neurological, or psychiatric disorders 45 . While the availability of neuropsychology is often limited, neuropsychologic testing can be helpful in identifying any underlying or exacerbation of a neurocognitive disorder requiring further therapeutic support (i.e., medication or speech or cognitive therapy).…”
Section: Rehabilitation and Long-term Managementmentioning
confidence: 99%
“…It has been demonstrated that the natural history of concussion, from 70% up to 85% of cases, is a spontaneous recovery within 2 weeks for adults and 4 weeks for children and adolescents. Patients will experiment with a natural reduction in symptoms by number and gravity through days, without any particular intervention [16,17]. This means that, after diagnosing a concussion, an observational approach could be part of the treatment process, as Nature is working on its own to promote spontaneous recovery.…”
Section: Migrainementioning
confidence: 99%
“…Protecting a patient from a second brain impact, especially if close to the one he/she is suffering, is mandatory. As said before after a brain injury, even if mild, the brain lays in a state of vulnerability [1], and a second impact could lead to a Second Impact Syndrome (SIS) or diffuse cerebral edema, with the greatest risk occurring in the first 10 days post-injury [16]. It is particularly true in sport-related concussion because of possible repetitive traumatic events [28], related to sports characteristics.…”
Section: Do Not Harm: Avoiding a Second Impactmentioning
confidence: 99%
“…School-sponsored contact sports are common activities among children and adolescents across the globe. However, with participation in contact sports comes the danger of head injuries, specifically concussions (Podolak et al, 2021). In the United States, it is estimated that between 1.6 million and 3.8 million sports-related concussions (SRCs) occur from sports each year (Halstead et al, 2018).…”
mentioning
confidence: 99%
“…In the United States, it is estimated that between 1.6 million and 3.8 million sports-related concussions (SRCs) occur from sports each year (Halstead et al, 2018). Of these SRCs, 1.1 million to 1.9 million occur in children 18 years of age or younger (Bryan et al, 2016; Podolak et al, 2021).…”
mentioning
confidence: 99%